2021
DOI: 10.1007/s00405-021-06935-x
|View full text |Cite
|
Sign up to set email alerts
|

A third hand to the surgeon: the use of an endoscope holding arm in endonasal sinus surgery and well beyond

Abstract: Background Extended endoscopic endonasal operations of the sinuses and the frontal skull base require a bimanual action of the surgeon in many cases. Thus, typically an assistant guides the endoscope and centers the field of view. In this study, we investigate in which cases an endoscope holding arm can be used alternatively. Materials and methods The electromagnetic system ENDOFIXexo was used in different surgical interventions of the paranasal sinuses an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The “EXPERT” was first presented in 2009 [ 21 ], and underwent subsequent improvements; in 2018, the “iArms” was jointly developed by Denso and Tokyo Women’s Medical University. Previously the Evolution 1 [ 22 ], Stewart Platform [ 23 ], Bresciea endoscope assistant robotic holder [ 24 ], Medineering [ 25 ], and ENDOFIX exo [ 26 ] were reported. These surgical robots feature a “hand-placement” function that follows the surgeon’s hand movements during surgery using a passive mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The “EXPERT” was first presented in 2009 [ 21 ], and underwent subsequent improvements; in 2018, the “iArms” was jointly developed by Denso and Tokyo Women’s Medical University. Previously the Evolution 1 [ 22 ], Stewart Platform [ 23 ], Bresciea endoscope assistant robotic holder [ 24 ], Medineering [ 25 ], and ENDOFIX exo [ 26 ] were reported. These surgical robots feature a “hand-placement” function that follows the surgeon’s hand movements during surgery using a passive mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not a routine solution for all situations, given its high cost. In some other types of surgeries, doctors have tried to invent an endoscopic holding arm to assist in the operation, but it is not applicable to all surgeries ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the ENDOFIX unites maneuverability, flexibility and stability. Thus, the surgeon can operate in a bimanual action-even in the absence of an assistant [23].…”
Section: Of 12mentioning
confidence: 99%